Kejadian Penyakit Busuk Pangkal Batang Ganoderma boninense: Sebuah Ulasan Pengetahuan, Persepsi dan Sikap Petani Kelapa Sawit - Hendarjanti, Henny (Seminar Nasional Lahan Suboptimal, 2024)
Hendarjanti, H. (2024). The incidence of ganoderma boninense basal stem rot disease: a review of knowledge, perception, and attitude of oil palm smallholders. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 958–968). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The palm oil industry has been the lifeblood of the Indonesian economy for decades. In 2023, around 40.75% of the land planted with oil palm is smallholder oil palm plantations. The expansion of oil palm causes instability in the ecosystem due to the monoculture planting system. The palm oil industry faces the problem of Basal Stem Rot (BSR) disease caused by the fungus Ganoderma boninense. This fungus can spread the disease through agents, which causes severe threats to the industry (Paterson & Lima, 2018). Smallholder oil palm plantations are also greatly affected, with the occurrence of BSR disease causing economic losses due to decreased production of fresh fruit bunches (FFB) and the death of oil palm trees. This study aimed to identify the level of knowledge, perception, and attitude of oil palm farmers towards the occurrence of BSR disease. A survey method through face-to-face interviews using a structured questionnaire was used to collect data from 110 respondents among independent smallholders in Musi Banyuasin, Ogan Komering Ilir and Muara Enim Regencies. The study showed that most independent smallholders only understood knowledge related to BSR disease after training. Smallholders need a better perception of the occurrence and management of BSR disease, which also affects smallholders' attitudes and actions in managing BSR disease. The findings of this study can be helpful for relevant authorities in identifying strategic programs to improve the knowledge and skills of oil palm smallholders in managing BSR disease.